2013
DOI: 10.1166/jbn.2013.1473
|View full text |Cite
|
Sign up to set email alerts
|

Functional Responses of Human Adipose Tissue-Derived Mesenchymal Stem Cells to Metal Oxide Nanoparticles <I>In</I> <I>Vitro</I>

Abstract: Nanoparticles (NPs) are frequently applied in biomedical applications. The use of human mesenchymal stem cells (hMSC) in biomedicine is pivotal, especially in oncology and tissue engineering. Titanium dioxide (TiO2) and zinc oxide (ZnO) NPs are interesting agents in experimental oncology and stem cells are discussed to be a potential vehicle for NPs to tumor sites. However, little is known about hazardous effects of NPs in hMSC. The aim of the present study was to analyze functional impairment of hMSC by ZnO- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…Cell migration is an important factor in the process of precise regulation between cell adhesion and dissociation from extracellular matrix proteins (34). Accordingly, inhibiting migration leads to distinct functional impairment, including influencing wound healing capacity (35). Zhou et al reported that ZnO nanoparticles impeded both cell migration and wound healing progress in both fibroblasts and epithelial cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration is an important factor in the process of precise regulation between cell adhesion and dissociation from extracellular matrix proteins (34). Accordingly, inhibiting migration leads to distinct functional impairment, including influencing wound healing capacity (35). Zhou et al reported that ZnO nanoparticles impeded both cell migration and wound healing progress in both fibroblasts and epithelial cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, S. Wang, Y. Wang, M. Xu, et al, 2009), Nano-films, plates and sheets (Bai, Sun, et al, 2013;Chougule, Sen, & Patil, 2012;, Nano-pyramids (Ahmad, Chang, Ahmad, Waclawik, & Wlodarski, 2013) and nanotetrapods (Calestani et al, 2010). These previous materials have been widely investigated and applied for gas sensing which are operating under the operating condition such as high electron mobility, high-specific surface area, non-toxic nature, good thermal and chemical stability (Hackenberg et al, 2013;Xie, He, Irwin, Jin, & Shi, 2011).…”
Section: Zno Gas Sensors For No X Detectingmentioning
confidence: 99%
“…The experiments also included control tubes containing only media and bacteria devoid of ZnO-NFs. [12][13] The morphology of bacterial suspension with and without NFs was observed with Bio-transmission electron (Bio-TEM) at 120 kv.…”
Section: Spectroscopic Characterization Of Zno Nanoflowersmentioning
confidence: 99%
“…11 Additionally, ZnO has been listed as a generally recognized as safe (GRAS) material by the U.S. Food and Drug Administration (21CFR182.8991). 12 13 As a GRAS material, ZnO also shows significant growth inhibition properties over a broad range of both gram-positive and gram-negative bacteria such as Escherichia coli, L. monocytogenes, S. enteritidis, B. subtillis, S. aureus, P. aeruginosa, E. faecalis, etc. 14 It was found that the interaction of ZnO nanomaterials with the bacteria resulted in the disruption of cell membrane integrity.…”
Section: Introductionmentioning
confidence: 99%